Isoalantolactone induces the apoptosis of oxaliplatin-resistant human colorectal cancer cells mediated by ROS generation and activation of JNK and p38 MAPK - Seung-On Lee; Sang Hoon Joo; Na Yeong Lee; Seung-Sik Cho; Goo Yoon; Ki-Taek Kim; Yung Hyun Choi; Jin Woo Park; Joon-Seok Choi; Jung-Hyun Shim (Scientific Reports)
Abstract Treating colorectal cancer (CRC) poses challenges due to the lack of specific molecular targets. Although oxaliplatin (Ox) is commonly used to treat CRC, resistance frequently develops, necessitating the discovery of new therapeutics. This study explored the anticancer effects of Isoalantolactone (IAL) on human CRC cells HCT116 and Ox-resistant HCT116 (HCT116-OxR). Apoptosis, ROS generation, cell cycle distribution, mitochondrial membrane potential (MMP), and caspase activation were assessed through flow cytometry. Protein levels were determined by Western blot analysis. IAL reduced cell viability, measured by MTT assay, and inhibited anchorage-independent colony formation in CRC cells in a time- and concentration-dependent manner. The IC50 values for 48 h of incubation were below 10 µM. Annexin V/7-AAD double staining demonstrated that IAL induced apoptosis in HCT116 and HCT116-OxR cells, and Western blot analysis confirmed increased phosphorylation of JNK and p38 mitogen-activated protein kinase (MAPK). The inhibition of these kinases by SP600125 or SB203580 blocked the antiproliferative effects of IAL. Additionally, IAL triggered ROS generation and disrupted mitochondrial membranes, leading to caspase activation. Pretreatment with N-acetylcysteine (NAC) or Z-VAD-FMK inhibited the antiproliferative effects of IAL, highlighting the crucial roles of ROS generation and caspase activation in IAL-induced apoptosis in CRC cells. In summary, IAL exhibited anticancer effects in CRC cells by inducing apoptosis by elevating ROS level and activating JNK and p38 MAPK. These findings warrant further study to evaluate the therapeutic potential of IAL in treating CRC with various resistances.